RISIKO DAN MODAL: PENGARUHNYA TERHADAP PROFITABILITAS (STUDI EMPIRIS PADA INDUSTRI PERBANKAN DI INDONESIA) - Bambang Sudiyatno; Titiek Suwarti; Toto Suharmanto; Okki Martinus (Dinamika Akuntansi Keuangan dan Perbankan, 2021)
This study discusses the effect of risk and capital on profitability of banks issued on the Indonesia Stock Exchange in the period of 2013-2017. The data used is panel data, which is a combination of time series data and cross section data. The method of taking data uses purposive sampling. Technical analysis was performed using multiple regression analysis. The results of the study show that credit risk (NPL) and operational risk (BOPO) have a negative and significant effect on profitability (ROA). While liquidity risk (LDR), market risk (NIM), and capital (CAR) do not affect on profitability (ROA). Furthermore credit risk (NPL), operational risk (BOPO) and capital (CAR) have a negative and significant effect on profitability (ROE), while liquidity risk (LDR) and market risk (NIM) do not affect on profitability (ROE). Keywords: profitability, liquidity risk, credit risk, market risk, operational risk and capital.